2017
DOI: 10.1038/s41467-017-00327-8
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells decrease efficacy of anti-angiogenic therapy by secreting matrix-degrading granzyme B

Abstract: Resistance towards VEGF-centered anti-angiogenic therapy still represents a substantial clinical challenge. We report here that mast cells alter the proliferative and organizational state of endothelial cells which reduces the efficacy of anti-angiogenic therapy. Consequently, absence of mast cells sensitizes tumor vessels for anti-angiogenic therapy in different tumor models. Mechanistically, anti-angiogenic therapy only initially reduces tumor vessel proliferation, however, this treatment effect was abrogate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 67 publications
2
51
1
Order By: Relevance
“…Next, we quantified the fraction of proliferating vessels after injection of BrdUrd. These analyses revealed an increase of BrdUrd þ vessels upon DC101 treatment compared with control treatment as previously described (27), whereas ATRA monotherapy had no effect (Fig. 3D).…”
Section: Atra Promotes Tumor Vessel Normalization and Maturationsupporting
confidence: 80%
“…Next, we quantified the fraction of proliferating vessels after injection of BrdUrd. These analyses revealed an increase of BrdUrd þ vessels upon DC101 treatment compared with control treatment as previously described (27), whereas ATRA monotherapy had no effect (Fig. 3D).…”
Section: Atra Promotes Tumor Vessel Normalization and Maturationsupporting
confidence: 80%
“…Wroblewski et al showed that MCs release FGF-2 that acts on ECs and induces their proliferation and promotes angiogenesis. The combination of cromolyn to prevent MC degranulation along with anti-angiogenic therapy promoted the therapeutic efficacy [74]. The engagement of TLR2 on MC has shown to stimulate tumor growth, and blocking this pathway may be promising in designing of immunotherapeutic strategies.…”
Section: Mcs As Therapeutic Targetsmentioning
confidence: 99%
“…Moreover, some patients on anti-VEGF drugs do not benefit (e.g., non-responders) and their vision continues to diminish. Insights into a mechanism underlying resistance observed in some AMD non-responders come from a recent article by Wroblewski et al that showed increased levels of GzmB from mast cells upon anti-VEGF treatment for cancer (tumor angiogenesis) (56). In Wroblewski et al, activity of extracellular GzmB was shown to liberate sequestered pro-angiogenic factors (from the tumor ECM) outside the VEGF-VEGFR2 axis.…”
Section: Gzmb's Putative Role In Amdmentioning
confidence: 99%